2013
DOI: 10.1016/j.bjane.2012.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Use of Simple Clinical Predictors on Preoperative Diagnosis of Difficult Endotracheal Intubation in Obese Patients

Abstract: The clinical and polysomnographic diagnosis of OSA proved useful in the preoperative diagnosis of difficult laryngoscopy. Obese patients are more prone to difficult facemask ventilation and laryngoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 18 publications
4
16
1
1
Order By: Relevance
“…Our study showed that the predictors for difficult airway management include BMI (continuous variable), cervical spine injury/fixation, history of difficult airway, head and neck mass, and oropharyngeal and/or supraglottic angioedema, which aligns with previous studies . The most interesting new finding from our study was that the otolaryngologists were able to prevent potential emergent surgical airways, as evidenced by a 71% decrease in the number of cricothyrotomies after establishment of the DART.…”
Section: Discussionsupporting
confidence: 87%
“…Our study showed that the predictors for difficult airway management include BMI (continuous variable), cervical spine injury/fixation, history of difficult airway, head and neck mass, and oropharyngeal and/or supraglottic angioedema, which aligns with previous studies . The most interesting new finding from our study was that the otolaryngologists were able to prevent potential emergent surgical airways, as evidenced by a 71% decrease in the number of cricothyrotomies after establishment of the DART.…”
Section: Discussionsupporting
confidence: 87%
“…In another study, investigators assessed Chinese females who were pregnant and those who were not pregnant and found that the combination of predictive variables could improve the validity. [6] A study from the USA found that by using as many as ten measurements, aggregate set of variables improved predictability of a difficult intubation. [7] Iohom et al .…”
Section: Discussionmentioning
confidence: 99%
“…One such challenge is difficulty with endotracheal intubation due to obesity and upper airway obstruction. In the adult population, it has been demonstrated that sleep apnea syndromes including OSA are independent risk factors for difficult endotracheal intubation [7,8]. In many patients, this relates not only to the weight or body mass index, but also correlates with the neck circumference.…”
Section: Discussionmentioning
confidence: 99%